Longitudinal Dynamics of Hydrological Connectivity in the Yellow River Delta, China - Xie, Chengjie; Cui, Baoshan; Ning, Zhonghua; Yu, Shuling; Xie, Tian (Frontiers in Marine Science, 2022)
River deltas are formed by the interaction of connecting water and sediment, and they are among the most economically and ecologically valuable ecosystems on Earth. Because of their special locations, together with direct and indirect human interference, river deltas are expected to be more vulnerable and fragmented. The increasing fragmentation of deltas is largely due to longitudinal hydrological connectivity disruption caused by human activities. However, the dynamics of longitudinal connectivity are unknown, especially in the Yellow River Delta (YRD), which has been subjected to heavy reclamation in recent years. In this study, we divided the whole YRD into three subregions, the erosion zone, the oilfield zone and the deposition zone, and then we used indicators to explore the spatiotemporal variation in hydrological connectivity on the whole scale and on the zonal scale of the delta during 1984-2018 in the YRD. We found that the variation in longitudinal hydrological connectivity was closely related to the geometry of the tidal channel networks, and that the changes in longitudinal hydrological connectivity varied with research scales. A weak increasing trend of connectivity was found on the whole scale of the delta during the past three decades. A decreasing trend of connectivity was found in both the erosion zone and the oilfield zone. In the deposition zone, however, the connectivity degree was enhanced. Furthermore, we also identified the key impaired area and relatively stable area of hydrological connectivity in the YRD and implied that the key impaired area may be a priority restoration zone of the impaired hydrological connectivity zone. Our study provides useful scientific guidance for the subsequent restoration of damaged wetlands.